2021
DOI: 10.3390/pr9111966
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Intraphase and Interphase Mass Transfer Limitations for NH3-SCR over Cu-ZSM-5

Abstract: A systematic modeling approach was scrutinized to develop a kinetic model and a novel monolith channel geometry was designed for NH3 selective catalytic reduction (NH3-SCR) over Cu-ZSM-5. The redox characteristic of Cu-based catalysts and the variations of NH3, NOx concentration, and NOx conversion along the axis in porous media channels were studied. The relative pressure drop in different channels, the variations of NH3 and NOx conversion efficiency were analyzed. The model mainly considers NH3 adsorption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Zhong et al [146] developed a model describing NH 3 -SCR-DeNO x and found that a small washcoat thickness (0.15 μm) and a large geometric surface area are advantageous leading to a reduction of the mass transfer limitation (Figure 3e). Yu and Zhang [147] developed a kinetic model and subsequent development of a novel Cu-ZSM-5 coated monolith channel for NH 3 -SCR-DeNO x . The hexagonal channel effectively increases the diffusion rate of reactants to the wall and the pressure drop resulting in improved catalytic activity.…”
Section: Micro-/mesoporous Zsm-5-based Catalystsmentioning
confidence: 99%
“…Zhong et al [146] developed a model describing NH 3 -SCR-DeNO x and found that a small washcoat thickness (0.15 μm) and a large geometric surface area are advantageous leading to a reduction of the mass transfer limitation (Figure 3e). Yu and Zhang [147] developed a kinetic model and subsequent development of a novel Cu-ZSM-5 coated monolith channel for NH 3 -SCR-DeNO x . The hexagonal channel effectively increases the diffusion rate of reactants to the wall and the pressure drop resulting in improved catalytic activity.…”
Section: Micro-/mesoporous Zsm-5-based Catalystsmentioning
confidence: 99%